Novel Molecular Imaging Approaches to Abdominal Aortic Aneurysm Risk Stratification. (January 2016) - Toczek, Jakub; Meadows, Judith L.; Sadeghi, Mehran M.
Abstract : Selection of patients for abdominal aortic aneurysm repair is currently based on aneurysm size, growth rate, and symptoms. Molecular imaging of biological processes associated with aneurysm growth and rupture, for example, inflammation and matrix remodeling, could improve patient risk stratification and lead to a reduction in abdominal aortic aneurysm morbidity and mortality. 18 F-fluorodeoxyglucose-positron emission tomography and ultrasmall superparamagnetic particles of iron oxide magnetic resonance imaging are 2 novel approaches to abdominal aortic aneurysm imaging evaluated in clinical trials. A variety of other tracers, including those that target inflammatory cells and proteolytic enzymes (eg, integrin αv β3 and matrix metalloproteinases), have proven effective in preclinical models of abdominal aortic aneurysm and show great potential for clinical translation.